Method for manufacturing nitride crystal substrate, and nitride crystal substrate
By forming a porous intermediate layer and a cover layer on the substrate, and epitaxial growth and peeling of the AlGaN regeneration layer are performed thereon, the problem of poor quality of the AlGaN substrate in the prior art is solved, and a stable acquisition of a high-quality crack-free AlGaN crystal substrate is achieved.
Patent Information
- Application Number
- CN202411255957.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-19
- Filing Date
- 2024-09-09
- Publication Date
- 2025-04-22
AI Technical Summary
It is difficult to stably obtain high-quality AlGaN-containing nitride crystal substrates, especially because the AlGaN layer does not match the lattice of the GaN or AlN crystal substrates, making it difficult to improve the device quality.
A manufacturing method is adopted, including forming an intermediate layer and a cover layer of n-type group III nitride crystal on the substrate, making the intermediate layer porous by electrochemical treatment, and then epitaxial growth of the AlGaN regeneration layer on the flat cover layer, and peeling the regeneration layer with the porous intermediate layer as the boundary.
A high-quality AlGaN crystal substrate with a crack-free crack is achieved, which relieves the crystal strain in the regeneration layer and improves the crystallinity and peelability of the substrate.
Smart Images

Figure CN119859847A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing a nitride crystal substrate and a nitride crystal substrate. Background Art
[0002] As a method for producing a nitride crystal substrate formed of a group III nitride crystal, various methods are disclosed (for example, Patent Document 1 and Non-Patent Document 1).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2003-178984
[0006] Non-patent literature
[0007] Non-patent literature 1: ECS Journal of Solid State Science and Technology 10(3), 035001, 2021 Summary of the invention
[0008] Problems to be solved by the invention
[0009] An object of the present invention is to stably obtain a nitride crystal substrate containing AlGaN.
[0010] Means of solving the problem
[0011] According to an embodiment of the present invention, there is provided a method for manufacturing a nitride crystal substrate, which comprises the following steps:
[0012] (a) a step of preparing a base substrate;
[0013] (b) forming an intermediate layer containing n-type group III nitride crystals on the base substrate;
[0014] (c) forming, on the intermediate layer, a cap layer containing a Group III nitride crystal having a carrier concentration lower than that of the intermediate layer;
[0015] (d) a step of maintaining the surface state of the covering layer and making the intermediate layer porous by dislocation of the covering layer through electrochemical treatment;
[0016] (e) a step of epitaxially growing a regrown layer including a group III nitride crystal on the cap layer;
[0017] (f) a step of peeling the regrown layer from the base substrate with at least a portion of the intermediate layer becoming porous as a boundary,
[0018] In (e), as the regrown layer, the Al composition ratio x is 0.05 or more and 0.8 or less. x Ga 1-x The crystal growth represented by the composition formula of N.
[0019] According to another aspect of the present invention, there is provided a nitride crystal substrate, wherein:
[0020] Contains Al x Ga 1-x A crystal represented by the composition formula of N,
[0021] The Al composition ratio x in the composition formula is 0.05 or more and 0.8 or less,
[0022] The nitride crystal substrate satisfies the following formula (1),
[0023] 0.58≤a / c≤0.66…(1)
[0024] Here,
[0025] c is the lattice constant in the <0001> axis direction of the nitride crystal substrate obtained by measuring the diffraction angle of a peak based on the (0002) plane diffraction of AlGaN by X-ray diffraction,
[0026] a is the lattice constant in the <11-20> axis direction of the nitride crystal substrate obtained based on c and the diffraction angle of the peak of the (10-12) plane diffraction of AlGaN obtained by X-ray diffraction measurement.
[0027] Effects of the Invention
[0028] According to the present invention, a nitride crystal substrate containing AlGaN can be stably obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 1 is a flowchart showing a method for manufacturing a nitride crystal substrate according to an embodiment of the present invention.
[0030] Figure 2A This is a schematic cross-sectional view showing a method for manufacturing a nitride crystal substrate according to an embodiment of the present invention.
[0031] Figure 2B This is a schematic cross-sectional view showing a method for manufacturing a nitride crystal substrate according to an embodiment of the present invention.
[0032] Figure 3A This is a schematic cross-sectional view showing a method for manufacturing a nitride crystal substrate according to an embodiment of the present invention.
[0033] Figure 3B This is a schematic cross-sectional view showing a method for manufacturing a nitride crystal substrate according to an embodiment of the present invention.
[0034] Figure 4 This is a schematic cross-sectional view showing a method for manufacturing a nitride crystal substrate according to an embodiment of the present invention.
[0035] Figure 5 This is a diagram showing temperature changes in the regrowth step according to one embodiment of the present invention.
[0036] Figure 6 This is a schematic cross-sectional view showing a method for manufacturing a nitride crystal substrate according to an embodiment of the present invention.
[0037] Figure 7 This is a schematic cross-sectional view showing a method for manufacturing a nitride crystal substrate according to an embodiment of the present invention.
[0038] Figure 8 This is a schematic cross-sectional view showing a method for manufacturing a nitride crystal substrate according to an embodiment of the present invention.
[0039] Fig. 9 This is a schematic cross-sectional view showing a method for manufacturing a nitride crystal substrate according to an embodiment of the present invention.
[0040] Fig. 10A This is a top view showing a nitride crystal substrate according to one embodiment of the present invention.
[0041] Fig. 10B : is a cross-sectional view showing a nitride crystal substrate according to one embodiment of the present invention.
[0042] Explanation of symbols
[0043] 10 Seed substrate for nitride crystal growth
[0044] 20 Stripping Intermediates
[0045] 50 Nitride crystal substrate
[0046] 100 Base Substrate
[0047] 120 main side
[0048] 200 bottom floor
[0049] 300 Middle Layer
[0050] 360 Gap
[0051] 400 Overlay
[0052] 500 Regrowth Layer
[0053] 520 First regrowth layer
[0054] 540 Second regrowth layer
[0055] 510 c side
[0056] 810 Electrolyte
[0057] 820 Processing Tank
[0058] 840 Power Supply
[0059] 842 Anode
[0060] 844 Cathode
[0061] 860 Ammeter DETAILED DESCRIPTION
[0062] <Knowledge of the Inventors>
[0063] A light emitting diode (LED) and a laser diode (LD) having a wavelength of about 365 nm to 530 nm (green) are realized by using a substrate formed of gallium nitride (GaN) crystal (hereinafter also referred to as a GaN crystal substrate).
[0064] On the other hand, ultraviolet LEDs and ultraviolet LDs with wavelengths shorter than 365nm need to grow a layer formed by aluminum gallium nitride (AlGaN) crystals containing aluminum (Al) (hereinafter also referred to as an AlGaN layer). However, when using the above-mentioned GaN crystal substrate, it is difficult to achieve high-quality devices because the lattice of the AlGaN layer does not match that of the GaN crystal substrate. In addition, as another case, there is also a case where an AlGaN layer is grown on an AlN crystal substrate prepared by a sublimation method such as that described in non-patent document 1. However, in this case, it is also difficult to achieve high-quality devices because the lattice of the AlGaN layer does not match that of the AlN crystal substrate. Therefore, it is desired to achieve a high-quality AlGaN crystal substrate.
[0065] Here, the GaN crystal substrate can be obtained, for example, by the VAS (Void-Assisted Separation) method described in the above-mentioned Patent Document 1. In the VAS method, first, a template is prepared, which has a GaN layer with voids and a mesh-shaped titanium nitride (TiN layer) in order on a sapphire substrate. Next, a thick GaN main growth layer is grown on the GaN layer and TiN layer in this state. Thereafter, the GaN main growth layer is peeled off from the substrate with the GaN layer with voids as the boundary. As a result, a GaN crystal substrate can be obtained from the peeled GaN main growth layer.
[0066] Alternatively, in order to obtain a GaN crystal substrate, a GaN main growth layer may be grown on a template whose surface of the GaN layer is partially covered by a mask having an opening.
[0067] In any of the above cases, at the initial stage of the growth of the GaN main growth layer, the GaN crystal grows in an island shape. Thereafter, when the thick GaN crystal grows, the island-shaped GaN crystals converge to obtain a GaN main growth layer as a continuous film. In the process of the convergence of the island-shaped GaN crystals, the crystal strain introduced during the growth of the thick GaN crystal is greatly relaxed. As a result, a crack-free thick GaN main growth layer can be grown even on a heterogeneous substrate.
[0068] Aluminum nitride (AlN) crystal substrates can be obtained by sublimation, for example, as described in non-patent document 1. In this case, first, in the initial stage, an AlN layer is grown on a heterogeneous substrate such as a silicon carbide (SiC) substrate. Next, the AlN layer is used as a seed and thickened by sublimation. Thereafter, an AlN crystal substrate is obtained by peeling off the heterogeneous substrate from the AlN layer. Once the AlN crystal substrate is obtained, the AlN crystal substrate is used as a seed and the AlN layer is grown by sublimation to obtain an AlN ingot. Thereafter, the AlN ingot is sliced to obtain an AlN crystal substrate.
[0069] On the other hand, the method of obtaining an AlGaN crystal substrate is more difficult than the method of obtaining a GaN crystal substrate or an AlN crystal substrate. First, because the vapor pressures of Al and Ga are different, it is extremely difficult to obtain an AlGaN crystal with a desired Al composition by sublimation. Therefore, the above-mentioned VAS method of growing an AlGaN main growth layer on a template is a realistic method. However, in this case, Al atoms are extremely difficult to move, and it is difficult to achieve a growth process including island growth, convergence of island crystals, and flattening of the crystal as in the case of GaN.
[0070] In particular, when the island-shaped AlGaN crystal grows three-dimensionally, as mentioned above, since the movement of Al atoms is small, parts with high Al composition ratio and parts with low Al composition ratio are generated in the plane. Therefore, crystal strain is likely to occur in the AlGaN main growth layer. As a result, cracks may occur in the AlGaN main growth layer.
[0071] Therefore, in order to obtain an AlGaN crystal substrate from an AlGaN main growth layer, a method is considered to first grow a thick GaN layer, flatten the surface of the GaN layer, and then grow a thick AlGaN main growth layer. However, even with this method, it is difficult to obtain a crack-free AlGaN main growth layer because of the lattice mismatch between the GaN layer and the AlGaN main growth layer.
[0072] Therefore, the inventors and others studied the following method as a method for manufacturing an AlGaN crystal substrate. First, an intermediate layer and a covering layer containing a group III nitride crystal are grown in sequence on a base substrate, and the stack is electrochemically treated. Thus, a seed substrate is prepared that maintains the flatness of the covering layer and makes the intermediate layer porous. Next, using the seed substrate, a regrown layer formed of AlGaN crystal as a continuous film is regrown on the flat covering layer. This method can solve the above-mentioned problems and successfully obtain a crack-free AlGaN crystal substrate from the regrown layer.
[0073] The present invention described below is based on the above-mentioned new knowledge discovered by the inventors.
[0074] <Details of Embodiments of the Invention>
[0075] Next, one embodiment of the present invention will be described below with reference to the drawings. Note that the present invention is not limited to these examples, and is intended to include all modifications within the meaning and scope of the claims and equivalents to the claims.
[0076] <One embodiment of the present invention>
[0077] Hereinafter, one embodiment of the present invention will be described with reference to the drawings.
[0078] (1) Method for manufacturing nitride crystal substrate
[0079] Reference Figures 1 to 9 , a method for manufacturing a nitride crystal substrate according to this embodiment is described.
[0080] Also, in Figure 2A to Figure 4 , Figure 6 to Figure 9 In the figure, hatching of the cross section other than the intermediate layer 300 is omitted.
[0081] Hereinafter, in a group III nitride crystal having a wurtzite structure, the <0001> axis (for example, the
[0001] axis) is referred to as the "c axis", and the (0001) plane is referred to as the "c plane". In addition, the (0001) plane is sometimes referred to as the "+c plane (group III element polar plane)", and the (000-1) plane is referred to as the "-c plane (nitrogen (N) polar plane)". The <1-100> axis is referred to as the "m axis", and the <11-20> axis is referred to as the "a axis". The so-called "carrier concentration" in the present invention means the free carrier concentration at room temperature (22°C).
[0082] like Figure 1As shown, the manufacturing method of the nitride crystal substrate of the present embodiment, for example, has the following steps: base substrate preparation step S10; bottom layer formation step S20; intermediate layer formation step S30; covering layer formation step S40; porous step S50; regrowth step S60; peeling step S70; post-processing step S80.
[0083] (S10: Substrate Preparation Step)
[0084] First, if Figure 2A As shown, a base substrate 100 is prepared.
[0085] In this embodiment, for example, a base substrate 100 formed of a material other than group III nitride is prepared. Specifically, as the base substrate 100, for example, a sapphire substrate, a SiC substrate, a silicon (Si) substrate, and a gallium arsenide (GaAs) substrate can be cited. In addition, the base substrate 100 can be insulating or conductive. Here, the base substrate 100 is, for example, a sapphire substrate.
[0086] The diameter of the base substrate 100 may be, for example, 1 inch (25 mm) or more, or 2 inches (50 mm) or more, or 4 inches (100 mm) or more, so that a large-area regrown layer 500 described later can be grown.
[0087] The thickness of the base substrate 100 is, for example, not less than 150 μm and not more than 3 mm.
[0088] The base substrate 100 has, for example, a main surface 120 as a growth surface. When the base substrate 100 is a sapphire substrate or a SiC substrate, the low-index crystal plane closest to the main surface 120 is, for example, a c-plane (+c-plane). When the base substrate 100 is a Si substrate or a GaAs substrate, the low-index crystal plane closest to the main surface 120 is, for example, a (001) plane or a (111) plane.
[0089] In this embodiment, the c-plane of the base substrate 100 may be inclined relative to the main surface 120. That is, the c-axis of the base substrate 100 may be inclined at a predetermined off angle relative to the normal to the main surface 120. The off angle of the base substrate 100 is, for example, not less than 0° and not more than 5°.
[0090] The arithmetic mean roughness (Ra) of the main surface 120 of the base substrate 100 is, for example, less than 0.3 nm.
[0091] (S20: Base layer forming step)
[0092] After the base substrate 100 is prepared, Figure 2AAs shown, for example, an underlying layer 200 containing a group III nitride crystal is formed on a base substrate 100 by a vapor phase growth method (forming an underlying layer 200 formed of a group III nitride crystal).
[0093] Specifically, for example, by the hydride vapor phase epitaxy (HVPE) method, aluminum chloride (AlCl3) gas and ammonia (NH3) gas are supplied to the base substrate 100 heated to a specified growth temperature, so that an aluminum nitride (AlN) buffer layer is grown. Next, gallium chloride (GaCl) gas and NH3 gas are supplied to the base substrate 100 heated to a specified growth temperature, so that a gallium nitride (GaN) layer is grown. In addition, the growth temperature of each layer is, for example, above 900°C and below 1100°C. Based on the above, an AlN buffer layer and a GaN layer are formed in sequence as a bottom layer 200 on the main surface 120 of the base substrate 100. However, the bottom layer 200 may not have an AlN buffer layer.
[0094] In this embodiment, the bottom layer 200 is made n-type, for example. Specifically, when the GaN layer as the bottom layer 200 is grown, dichlorosilane (SiH2Cl2) gas is further supplied as an n-type doping gas to grow the Si-doped GaN layer.
[0095] In this embodiment, the carrier concentration in the GaN layer in the bottom layer 200 is lower than the carrier concentration in the middle layer 300, for example. In other words, the n-type impurity concentration in the GaN layer in the bottom layer 200 is lower than the n-type impurity concentration in the middle layer 300, for example. Specifically, the carrier concentration (and n-type impurity concentration) in the bottom layer 200 is set to, for example, 2×10 18 cm -3 Below, or 1×10 18 cm -3 As a result, in the porous step S50 of making the intermediate layer 300 porous by electrochemical treatment, which will be described later, the base layer 200 can function as an etching stop layer under the intermediate layer 300 .
[0096] The lower limit of the carrier concentration in the GaN layer in the bottom layer 200 is not limited. However, the carrier concentration in the GaN layer in the bottom layer 200 can be set to, for example, 1×10 16 cm -3 As described above, since the base layer 200 itself has some conductivity, in the porous step S50 described later, the etching of the intermediate layer 300 can be carried out toward the lower part of the intermediate layer 300 by electrochemical treatment.
[0097] The thickness of the base layer 200 is not particularly limited. However, the thickness of the base layer 200 can be, for example, greater than 0 nm and less than 5 μm. By making the thickness of the base layer 200 less than 5 μm, the total thickness of the stacked layers on the base substrate 100 can be adjusted to, for example, less than 15 μm. Thus, cracks caused by the difference in linear expansion coefficients of the base substrate 100 and the base layer 200 can be suppressed.
[0098] In this embodiment, the c-plane of the GaN layer is the closest low-index crystal plane to the surface of the base layer 200. By forming the surface of the base layer 200 flat with such a crystal plane in advance, the intermediate layer 300 and the cap layer 400 with good crystallinity can be grown on the surface of the base layer 200.
[0099] (S30: Intermediate Layer Formation Step)
[0100] After forming the bottom layer 200, if Figure 2B As shown, for example, by vapor phase growth method, an intermediate layer 300 containing n-type group III nitride crystal is formed on the bottom layer 200 located above the base substrate 100. (In this process, the intermediate layer 300 formed of the group III nitride crystal in a state without including voids is formed.)
[0101] Specifically, for example, by the HVPE method, GaCl gas, NH3 gas, and SiH2Cl2 gas as an n-type doping gas are supplied to the base substrate 100 heated to a predetermined growth temperature, thereby growing a Si-doped GaN layer as the intermediate layer 300 on the bottom layer 200. The intermediate layer 300 grows with the +c plane as the growth plane.
[0102] In this embodiment, the carrier concentration in the intermediate layer 300 is made higher than the carrier concentration in the bottom layer 200 and the carrier concentration in the cover layer 400, for example. In other words, the n-type impurity concentration in the intermediate layer 300 is made higher than the n-type impurity concentration in the bottom layer 200 and the n-type impurity concentration in the cover layer 400, for example. Specifically, the carrier concentration (and n-type impurity concentration) in the intermediate layer 300 may be, for example, 3×10 18 cm -3 or more, or 1×10 19 cm -3 As described above, the intermediate layer 300 can be selectively made porous in the porous step S50 described later.
[0103] There is no upper limit to the carrier concentration in the intermediate layer 300. However, the carrier concentration in the intermediate layer 300 may be, for example, 1×10 20 cm -3 Below, or 5×10 19 cm-3 Thereby, it is possible to suppress the decrease in the crystallinity of the intermediate layer 300 .
[0104] In this embodiment, the thickness of the intermediate layer 300 can be, for example, higher than 100 nm, or can be greater than 500 nm, or can be greater than 1 μm. Thus, in the porous step S50 described later, large voids can be formed in the intermediate layer 300. Thus, in the regrowth step S60 described later, the voids 360 of the intermediate layer 300 can be maintained. As a result, in the peeling step S70 described later, the regrown layer 500 can be easily and stably peeled off from the base substrate 100 with at least a portion of the intermediate layer 300 maintained in the porous state as a boundary.
[0105] The upper limit of the thickness of the intermediate layer 300 is not limited. However, the thickness of the intermediate layer 300 can be, for example, 10 μm or less. By making the thickness of the intermediate layer 300 10 μm or less, the total thickness of the stack on the base substrate 100 can be adjusted to, for example, 15 μm or less. Thus, cracks caused by the difference in linear expansion coefficients of the base substrate 100 and the intermediate layer 300 and other layers can be suppressed.
[0106] (S40: Covering Layer Forming Step)
[0107] After forming the intermediate layer 300, as Figure 3A As shown, for example, a cap layer 400 containing a group III nitride crystal is formed on the intermediate layer 300 by a vapor phase growth method (cap layer 400 formed of a group III nitride crystal is formed).
[0108] In this embodiment, for example, GaN crystal is grown as the cap layer 400. Thus, the crystal growth of the cap layer 400 can be easily controlled by the vapor phase growth method. As a result, the crystallinity of the cap layer 400 can be stably improved. In addition, the carrier concentration of the cap layer 400 can be easily controlled.
[0109] Specifically, for example, by the HVPE method, a Si-doped GaN layer is grown as a cap layer 400 on the intermediate layer 300 under the same conditions as those in the intermediate layer forming step S30, except that the supply amount of SiH2Cl2 gas as the n-type doping gas is less than that in the intermediate layer forming step S30. The cap layer 400 is grown with the +c plane as the growth plane.
[0110] In this embodiment, the carrier concentration in the cap layer 400 is set to be, for example, lower than the carrier concentration in the intermediate layer 300. In other words, the n-type impurity concentration in the cap layer 400 is set to be, for example, lower than the n-type impurity concentration in the intermediate layer 300. Specifically, the carrier concentration (and the n-type impurity concentration) in the cap layer 400 is set to be, for example, 1×1018 cm -3 Thus, in the porous step S50 described later, the etching of the cover layer 400 can be suppressed and the intermediate layer 300 can be selectively porous. That is, under a predetermined voltage, the size of the voids 360 of the intermediate layer 300 can be increased and the enlargement of the micro voids of the cover layer 400 can be avoided.
[0111] The lower limit of the carrier concentration in the cover layer 400 is not limited. However, the carrier concentration in the cover layer 400 may be, for example, 1×10 16 cm -3 or more, or 1×10 17 cm -3 As described above, since the cover layer 400 itself is also conductive, in the electrochemical treatment of the porous step S50 to make the intermediate layer 300 porous, the intermediate layer 300 can be connected to the anode 842 via the cover layer 400 and the intermediate layer 300 as a whole can be at the same potential as the anode 842 .
[0112] Here, in the state where the cover layer forming step S40 is completed, the base layer 200, the intermediate layer 300, and the cover layer 400, for example, have a plurality of dislocations D penetrating in the thickness direction. The dislocation density on the surface of the cover layer 400 is, for example, 1×10 8 cm -2 Above and 1×10 9 cm -2 The dislocation D of the cover layer 400 is utilized in the following porous step S50.
[0113] In the present embodiment, the thickness of the cover layer 400 may be, for example, not less than 10 nm and not more than 2 μm, or not less than 50 nm and not more than 1.5 μm.
[0114] By making the thickness of the cover layer 400 10 nm or more, or 50 nm or more, even if outgassing of N2 gas or the like occurs when etching the intermediate layer 300 in the porous step S50 described later, the cover layer 400 can be maintained, and the outgassing can be discharged to the outside of the cover layer 400 through the dislocation D of the cover layer 400. Thus, the peeling of the cover layer 400 from the intermediate layer 300 can be suppressed.
[0115] On the other hand, by setting the thickness of the cover layer 400 to 2 μm or less, or 1.5 μm or less, the electrolyte can stably reach the intermediate layer 300 through the dislocations D of the cover layer 400 in the porous step S50 described later. Thus, the voids in the intermediate layer 300 can be stably formed.
[0116] After the capping layer 400 is grown, the temperature of the base substrate 100 is lowered from the growth temperature of the group III nitride crystal to room temperature. Thus, a stacked body including the base substrate 100, the base layer 200, the intermediate layer 300, and the capping layer 400 can be formed.
[0117] At this time, if Figure 3B As shown, the stacked body as a whole warps due to the difference in linear expansion coefficients between the base substrate 100 and the group III nitride crystal layer including the bottom layer 200, the intermediate layer 300 and the cover layer 400. Specifically, the linear expansion coefficient of sapphire as the base substrate 100 is greater than the linear expansion coefficient of the group III nitride, so the stacked body as a whole warps in a manner that the surface of the cover layer 400 is convex.
[0118] The above bottom layer forming step S20, the intermediate layer forming step S30, and the cover layer forming step S40 are performed continuously in the same chamber without exposing the base substrate 100 to the atmosphere. As a result, it is possible to suppress the accidental mixing of at least one of oxygen (O) and silicon (Si) as n-type impurities at the interface between the bottom layer 200, the intermediate layer 300, and the cover layer 400. As a result, the influence on the carrier concentration in these layers can be suppressed.
[0119] (S50: Multi-hole process)
[0120] After forming the cover layer 400, as Figure 4 As shown, the surface state of the cover layer 400 is maintained by the electrochemical treatment, and the intermediate layer 300 is made porous by the dislocation D of the cover layer 400 .
[0121] Specifically, for example, the electrochemical treatment is performed according to the following procedure.
[0122] like Figure 4 As shown, first, a processing tank 820, a power supply 840, and an ammeter 860 are prepared. The power supply 840 and the ammeter 860 may be assembled into one device as a current and voltage power supply.
[0123] The treatment tank 820 is filled with an electrolyte 810. The electrolyte 810 is a solution containing ions that can electrochemically etch the group III nitride. Examples of the electrolyte 810 include aqueous solutions containing oxalic acid, nitric acid, hydrofluoric acid, sulfuric acid, sodium sulfate (Na2SO4), sodium chloride (NaCl), sodium hydroxide (NaOH), etc. Here, the electrolyte 810 is an oxalic acid solution.
[0124] In addition, electrodes for electrochemical treatment are prepared. Specifically, in the laminated body after the above-mentioned covering layer forming step S40 is completed, an anode 842 is provided on the surface of the covering layer 400, and the anode 842 is connected to the power supply 840. On the other hand, a cathode 844 is prepared, and the cathode 844 is connected to the power supply 840. As the cathode 844, a material that is both corrosion-resistant and easy to flow current is used. As a specific cathode 844, for example, stainless steel (SUS), platinum (Pt), gold (Au), and boron-doped diamond can be cited.
[0125] After the connection of each electrode is completed, the stacked body connected with the anode 842 and the cathode 844 is immersed in the electrolyte 810 in the treatment tank 820. In this state, a predetermined voltage is applied between the anode 842 and the cathode 844 by the power supply 840. Thus, the electrochemical treatment is performed. At this time, the progress of the electrochemical treatment is confirmed based on the change of the current of the ammeter 860.
[0126] At this time, through the electrochemical treatment, the C2O4 2- The electrolyte passes through the dislocation D of the cover layer 400 with a relatively low carrier concentration and penetrates toward the intermediate layer 300 with a relatively high carrier concentration. That is, the dislocation D of the cover layer 400 is used as a nano-sized path for the electrolyte to penetrate. The intermediate layer 300 is selectively etched by the electrolyte that reaches the intermediate layer 300 in this way. As a result, a plurality of voids 360 are formed near the plurality of dislocations D in the intermediate layer 300. As a result, the intermediate layer 300 can be made porous.
[0127] On the other hand, according to the following reaction formula, the group III element ions (Ga 3+ ), and nitrogen (N 2 ) gas are released to the outside of the cover layer 400 through the dislocation D of the cover layer 400 .
[0128] 2GaN+6h + →2Ga 3+ +N2
[0129] Through the above-mentioned electrochemical treatment, each of the plurality of voids 360 in the intermediate layer 300 is formed, for example, at a position overlapping each of the plurality of dislocations D in the cover layer 400 described later. The plurality of voids 360 in the intermediate layer 300, for example, extend from the lower surface of the cover layer 400 in the thickness direction toward the base substrate 100. In addition, the voids 360 may not reach the base layer 200.
[0130] On the other hand, the partition wall portion other than the voids 360 of the intermediate layer 300 connects the upper portion of the base layer 200 or the lower portion of the intermediate layer 300 to the cover layer 400. Thus, even if the intermediate layer 300 has a plurality of voids 360, a constant thickness can be maintained.
[0131] At this time, in the present embodiment, the length of each of the plurality of voids 360 in the intermediate layer 300 along the main surface 120 of the base substrate 100 is, for example, 30 nm or more, or 100 nm or more when viewing any cross section perpendicular to the main surface 120 of the base substrate 100. Thus, in the regrowth step S60 described later, the voids 360 of the intermediate layer 300 can be maintained. As a result, in the peeling step S70 described later, the regrown layer 500 can be easily and stably peeled off from the base substrate 100 with at least a portion of the intermediate layer 300 that maintains a porous state as a boundary.
[0132] There is no upper limit to the length of the void 360 in the intermediate layer 300 along the main surface 120 of the base substrate 100. However, the length of the void 360 along the main surface 120 of the base substrate 100 may be 10 μm or less. Thus, by appropriately adjusting the electrochemical treatment conditions in the porous step S50, it is possible to suppress the peeling of the cover layer 400 caused by outgassing generated when etching the intermediate layer 300.
[0133] At this time, in the present embodiment, the depth of each of the plurality of voids 360 in the thickness direction of the intermediate layer 300 is, for example, greater than 100 nm, or greater than 500 nm, or greater than 1 μm. Thus, in the regrowth step S60 described later, the voids 360 of the intermediate layer 300 can be maintained. As a result, in the peeling step S70 described later, the regrown layer 500 can be easily and stably peeled off from the base substrate 100.
[0134] The upper limit of the depth of the void 360 is not limited. However, the depth of the void 360 may be less than the thickness of the intermediate layer 300. Thus, in the peeling step S70 described later, it is possible to suppress the excessive extension of the peeling from the intermediate layer 300 to other layers.
[0135] On the other hand, in this electrochemical treatment, etching hardly occurs on the surface of the cover layer 400 having a relatively low carrier concentration. In other words, even if the cover layer 400 has a plurality of dislocations D as described above, excessive etching does not occur on the surface near the dislocations D of the cover layer 400. Thus, the surface state of the cover layer 400 can be maintained flat.
[0136] At this time, in this embodiment, after the porous process S50, the arithmetic mean roughness (Ra) of the surface of the covering layer 400 is, for example, 1.0 nm or less, and the root mean square roughness (RMS) of the surface of the covering layer 400 is, for example, 2.0 nm or less. Alternatively, the Ra of the surface of the covering layer 400 may be, for example, 0.5 nm or less, and the RMS of the surface of the covering layer 400 may be, for example, 1.0 nm or less. Here, Ra and RMS are values when the surface of the covering layer 400 is observed in a 5 μm square field of view using an atomic force microscope (AFM).
[0137] As described above, by maintaining the surface roughness of the cap layer 400 at a low level, the thick regrown layer 500 having good crystallinity can be stably grown on the cap layer 400 .
[0138] The lower limits of Ra and RMS of the surface of the cover layer 400 are not limited and may be close to Ra and RMS of the main surface 120 of the base substrate 100. Specifically, the lower limits of Ra and RMS of the surface of the cover layer 400 may be 0.1 nm and 0.2 nm, respectively.
[0139] As specific conditions for the electrochemical treatment that can achieve the selective etching of the intermediate layer 300, for example, the following can be cited. The treatment voltage is adjusted based on the carrier concentration of the intermediate layer 300, etc. The treatment current is adjusted based on the treatment area (the area of the base substrate 100). The treatment time is adjusted based on the thickness of the intermediate layer 300.
[0140] Electrolyte temperature: room temperature (above 10°C and below 30°C)
[0141] Processing voltage: 1V or more and 200V or 10V or more and 20V or less Processing current: 0.01mA or more and 60A or more and 10A or less Processing time: 0.1min or more and 180min or more and 1min or more and 30min or less
[0142] As the intermediate layer 300 is subjected to the electrochemical treatment described above, it becomes porous. Figure 4 As shown, the cover layer 400 is separated from the laminated body including the base substrate 100 and the bottom layer 200 by sandwiching the porous intermediate layer 300. Since the voids 360 of the intermediate layer 300 have the above-mentioned size, the separation can be significantly performed.
[0143] Thus, the warping of the cover layer 400 in the porous step S50 can be reduced compared to the warping of the cover layer 400 before the porous step S50. That is, the cover layer 400 can be brought into a nearly flat state.
[0144] On the other hand, seed substrate 10 is in a state close to a thin structure of the group III nitride crystal layer on base substrate 100. Thus, warpage of base substrate 100 in porous step S50 can be reduced compared to warpage of base substrate 100 before porous step S50.
[0145] After the electrochemical treatment, the nitride crystal growth seed substrate 10 is taken out from the electrolyte in the treatment tank 820. Thereafter, the nitride crystal growth seed substrate 10 taken out from the treatment tank 820 is washed with pure water or the like and dried. Thus, the electrolyte remaining in the gaps 360 of the intermediate layer 300 is removed. Based on the above, the porous step S50 is completed.
[0146] In this way, a seed substrate 10 is obtained. This seed substrate 10 is used in the regrowth step S60 and the peeling step S70 described later.
[0147] (S60: Regrowth Step)
[0148] After the porous step S50 is completed, a regrown layer 500 formed of a group III nitride crystal is epitaxially grown on the cap layer 400. As a method for growing the regrown layer 500, for example, a vapor phase growth method is used.
[0149] In this embodiment, the regrown layer 500 is made of Al having an Al composition ratio x of 0.05 or more and 0.8 or less. x Ga 1-x The crystal growth represented by the composition formula of N.
[0150] In this embodiment, the regrown layer 500 formed of the AlGaN crystal is grown on the flat cap layer 400 on the porous intermediate layer 300 , and the crystal strain generated in the regrown layer 500 can be alleviated compared to the case where the porous step S50 is not performed.
[0151] On the other hand, in this embodiment, by setting the Al composition ratio x of the regrown layer 500 to 0.05 or more and 0.8 or less, appropriate crystal strain can be applied to the porous intermediate layer 300. As a result, the peeling property of the regrown layer 500 with the intermediate layer 300 as a boundary can be improved.
[0152] In the regrowth step S60 of this embodiment, Figure 5 As shown, the growth temperature may be adjusted in two stages. Specifically, the regrowth step S60 may include, for example, a first regrowth step S62 and a second regrowth step S64.
[0153] In this case, in the regrowth step S60, first, Figure 5 As shown, the temperature of the seed substrate 10 is raised from room temperature to the first growth temperature T1.
[0154] (S62: First Regrowth Step)
[0155] After the temperature of the seed substrate 10 reaches the first growth temperature T1, Figure 6 As shown, the first regrown layer 520 is grown on the capping layer 400 at the first growth temperature T1.
[0156] Specifically, for example, by the HVPE method, AlCl3 gas, GaCl gas, and NH3 gas are supplied to the seed substrate 10 heated to the first growth temperature T1, so that the AlGaN layer is grown. Thus, the AlGaN layer is epitaxially grown as the first regrown layer 520 on the surface of the cap layer 400. In addition, various dopants may be added to the AlGaN layer as the first regrown layer 520.
[0157] At this time, in this embodiment, the first growth temperature T1 of the first regrowth step S62 is set lower than the second growth temperature T2 of the second regrowth step S64 as the main growth described later. That is, the first growth temperature T1 of the first regrowth step S62 is set lower than the growth temperature of a typical III-nitride crystal.
[0158] At this time, as the temperature rises from room temperature to the first growth temperature T1, the base substrate 100 stretches. However, because the first growth temperature T1 is low (lower than the growth temperature of the bottom layer 200, etc.), the base substrate 100 cannot be completely flat, and the main surface 120 of the base substrate 100 remains in a state of slight protrusion.
[0159] In contrast, since the linear expansion coefficient of the cover layer 400 is smaller than that of the base substrate 100, the elongation of the cover layer 400 is smaller than that of the base substrate 100. Therefore, the cover layer is warped in a manner that the surface of the cover layer 400 is recessed. However, since the first growth temperature T1 is low, excessive warping of the cover layer 400 can be suppressed. Thus, the occurrence of cracks in the cover layer 400 can be suppressed. As a result, the occurrence of cracks in the regrown layer 500 on the cover layer 400 can be suppressed.
[0160] At this time, in this embodiment, the first growth temperature T1 is set to, for example, 970° C. or less. Thus, in the first regrowth step S62 , cracking of the cover layer 400 can be stably suppressed. As a result, cracking of the regrown layer 500 on the cover layer 400 can be stably suppressed.
[0161] On the other hand, the first growth temperature T1 may be set to, for example, 800° C. or higher. This allows the group III nitride crystal serving as the first regrown layer 520 to grow stably.
[0162] As described above, by adjusting the first growth temperature T1, the first regrown layer 520 of a predetermined thickness can be grown on the cover layer 400 while cracking of the cover layer 400 is suppressed. As a result, the total thickness of the group III nitride crystal layer (cover layer 400 and first regrown layer 520) formed on the porous intermediate layer 300 can be stably increased. As a result, in the second regrowing step S64 as the main growth described later, when the temperature is raised to the second growth temperature T2, the group III nitride crystal layer on the intermediate layer 300 can be made less likely to crack.
[0163] At this time, in the present embodiment, the growth of the first regrown layer 520 is started on the cap layer 400 having a flat surface, and at least in the initial growth stage (thin stage) of the first regrown layer 520 as the regrown layer 500, the regrown layer 500 can be made to perform step flow growth. That is, in the initial growth stage, the island growth of the regrown layer 500 formed of the AlGaN crystal can be suppressed. Thus, the regrown layer 500 formed of the AlGaN crystal as a continuous film can be made to perform step flow growth with the c-plane 522 (+c-plane) as the growth plane over the entire surface of the cap layer 400. As a result, the Al composition ratio x can be made uniform within the plane of the first regrown layer 520. In addition, the crystallinity of the first regrown layer 520 can be improved.
[0164] Thereafter, after the step flow growth in the initial stage of the growth of the first regrown layer 520, when the first regrown layer 520 is gradually grown, an inclined interface other than the c-plane may be generated in at least a portion of the first regrown layer 520. That is, after the first regrown layer 520 of a predetermined thickness is subjected to step flow growth, the first regrown layer 520 may be three-dimensionally grown. Thus, at least a portion of the plurality of dislocations D propagating from the cap layer 400 along the c-axis direction of the first regrown layer 520 can be bent and propagated in a direction substantially perpendicular to the inclined interface at a position where the inclined interface is exposed. Thus, at least a portion of the plurality of dislocations D can be locally concentrated. By making the locally concentrated dislocations D disappear from each other, the dislocation density can be reduced. As a result, the number of pits on the surface of the regrown layer 500 can be reduced.
[0165] At this time, in this embodiment, the thickness of the first regrown layer 520 can be, for example, 1 μm or more, or 10 μm or more, or 20 μm or more. Thus, in the second regrowing step S64 as the main growth described later, when the temperature is raised to the second growth temperature, the III-nitride crystal layer above the intermediate layer 300 can be stably prevented from cracking.
[0166] On the other hand, the upper limit of the thickness of the first regrown layer 520 is not particularly limited. However, the thickness of the first regrown layer 520 may be, for example, 300 μm or less, or 100 μm or less.
[0167] When the thickness of the first regrown layer 520 reaches a predetermined thickness, the supply of the AlCl 3 gas and the GaCl gas is stopped to terminate the growth of the first regrown layer 520. In addition, the supply of the NH 3 gas is continued.
[0168] Afterwards, if Figure 5 As shown, the temperature of the seed substrate 10 is raised from the first growth temperature T1 to the second growth temperature T2.
[0169] (S64: Second Regrowth Step)
[0170] After the temperature of the seed substrate 10 is raised from the first growth temperature T1 to the second growth temperature T2, as shown in FIG. Figure 7 As shown, the growth of the regrown layer 500 as the second regrown layer 540 is restarted. That is, at the second growth temperature T2, the thick second regrown layer 540 is grown on the first regrown layer 520 as the main growth.
[0171] Specifically, for example, the second regrowth step S64 is performed in the same chamber as the first regrowth step S62 without exposure to the atmosphere. In the second regrowth step S64, an AlGaN layer is epitaxially grown as the second regrowth layer 540 on the first regrowth layer 520 under the same conditions as the first regrowth step S62, except that the growth temperature is the second growth temperature T2. In addition, various dopants may be added to the AlGaN layer as the second regrowth layer 540.
[0172] At this time, in the present embodiment, as described above, even if the second growth temperature T2 of the second regrowth step S64 as the main growth is higher than the first growth temperature T1 of the first regrowth step S62, the group III nitride crystal layer above the intermediate layer 300 is less likely to crack because the total thickness of the cap layer 400 and the first regrowth layer 520 as the group III nitride crystal layer above the intermediate layer 300 is thicker. As a result, the regrowth layer 500 can be stably grown.
[0173] At this time, in this embodiment, as described above, by making the second growth temperature T2 of the second regrowth step S64 higher than the first growth temperature T1, the second regrowth layer 540 can be stably step-flow grown (two-dimensional growth, lateral growth) with the c-plane 542 as the growth plane. As a result, the flatness of the surface can be improved, and the second regrowth layer 540 with good crystallinity and thick film can be grown. In addition, the normal line of the c-plane 542 of the second regrowth layer 540, that is, the c-axis, can be tilted at an off-angle inherited from the c-axis of the base substrate 100 tilted at a predetermined off-angle.
[0174] At this time, in this embodiment, the second growth temperature T2 can be set to, for example, 980° C. or higher, or 1000° C. or higher. Thus, the second regrown layer 540 can be stably step-flow grown. As a result, the flatness of the second regrown layer 540 can be improved, and the second regrown layer 540 with good crystallinity and thick film can be stably grown.
[0175] On the other hand, the second growth temperature T2 can be set to, for example, 1200° C. or less. This can suppress the surface roughness of the second regrown layer 540 caused by an excessively high growth temperature.
[0176] At this time, in the first regrowing step S62 of the present embodiment, when at least a portion of the first regrown layer 520 has an inclined interface (when the first regrown layer 520 is grown three-dimensionally), the second regrown layer 540 is grown laterally as described above, so that the inclined interface of the second regrown layer 540 can be gradually reduced, that is, the c-plane 542 can be gradually expanded. Thus, the second regrown layer 540 having a mirror-finished surface can be grown.
[0177] At this time, in this embodiment, the total thickness of the regrown layer 500 (the first regrown layer 520 and the second regrown layer 540) can be, for example, 600 μm or more, or can be 1 mm or more. The upper limit of the total thickness of the regrown layer 500 is not particularly limited. However, from the perspective of improving productivity, the total thickness of the regrown layer 500 can be, for example, 100 mm or less.
[0178] Here, during the growth of the thick regrown layer 500, the dislocations D move in a random walk. As a result, during the growth of the regrown layer 500, the dislocations D converge with each other or form loops. By utilizing such a phenomenon, the dislocations D reaching the surface of the thick second regrown layer 540 can be reduced.
[0179] Alternatively, in the first regrowing step S62 of the present embodiment, even when an inclined interface is generated in at least a portion of the first regrown layer 520 (when the first regrown layer 520 is grown three-dimensionally), dislocations can be locally concentrated at the convergence portion of adjacent inclined interfaces during the lateral growth of the second regrown layer 540. In this case, the dislocations D reaching the surface of the thick second regrown layer 540 can also be reduced.
[0180] As a result, the dislocation density of the second regrown layer 540 can be reduced. Figure 7 After simplification, Figure 7 The number of dislocations in the sample did not decrease much.)
[0181] (S70: Peeling Step)
[0182] After the regrowth step S60 is completed, Figure 8 As shown, the regrown layer 500 is peeled off from the base substrate 100 with at least a portion of the intermediate layer 300 formed in a porous state as a boundary.
[0183] In this embodiment, during the temperature drop after the regrowth step S60, the regrown layer 500 is spontaneously peeled off from the base substrate 100. Thus, a special additional step of peeling off is not required. That is, the manufacturing method can be simplified.
[0184] Here, in the regrowth step S60, tensile stress occurs in the regrowth layer 500 (in the direction along the main surface 120 of the base substrate 100). This is caused, for example, by the decrease in dislocation density as the thickness of the regrowth layer 500 increases as described above.
[0185] The tensile stress generated in the regrown layer 500 in the direction along the main surface 120 of the base substrate 100 causes the c-plane 510 of the regrown layer 500 to be warped into a spherical shape with a concave upper side. As a result, the regrown layer 500 is spontaneously and gradually peeled off from the periphery toward the center of the base substrate 100. That is, by utilizing the warping of the c-plane 510 of the regrown layer 500, the regrown layer 500 can be gradually peeled off from the periphery toward the center of the base substrate 100. In other words, the regrown layer 500 can be peeled off uniformly in a concentric circle with respect to the center of the base substrate 100. As a result, the regrown layer 500 of a large area can be easily and stably peeled off.
[0186] Through the above-described peeling step S70, the peeling intermediate body 20 having at least the cap layer 400 and the regrown layer 500 is formed. On the lower surface of the cap layer 400 of the peeling intermediate body 20, a residual piece of the intermediate layer 300 may be left.
[0187] (S80: post-processing step)
[0188] After the stripping step S70 is completed, Fig. 9 As shown, for example, the regrown layer 500 is sliced with a wire saw along a cut plane perpendicular to the normal direction of the center of the surface of the regrown layer 500. Thus, a nitride crystal substrate 50 (hereinafter sometimes simply referred to as "substrate 50") as an as-cut substrate is formed.
[0189] Next, both surfaces of the substrate 50 are polished by a polishing device, thereby making the main surface of the substrate 50 mirror-finished.
[0190] Through the above steps, the substrate 50 formed of AlGaN crystal according to the present embodiment can be obtained.
[0191] (Process for manufacturing laminated product or semiconductor device)
[0192] Thereafter, a laminate or semiconductor device can be manufactured using the above-mentioned substrate 50. The laminate or semiconductor device, for example, comprises the above-mentioned substrate 50 and a semiconductor layer containing a group III nitride crystal provided on the substrate 50. Thus, for example, a high-quality semiconductor device such as an ultraviolet LED or an ultraviolet LD can be manufactured.
[0193] (2) Nitride crystal substrate
[0194] Reference Fig. 10A and Fig. 10B , the nitride crystal substrate 50 of this embodiment is described.
[0195] In this embodiment, the substrate 50 is made of, for example, Al x Ga 1-x The crystal represented by the composition formula of N is formed. The Al composition ratio x in the composition formula of the substrate 50 is, for example, 0.05 or more and 0.8 or less.
[0196] By setting the Al composition ratio x in the composition formula of the substrate 50 to be 0.05 or more and 0.8 or less, the peeling property of the regrown layer 500 with the intermediate layer 300 as a boundary can be improved as described above, and the substrate 50 can be stably obtained from the regrown layer 500 .
[0197] From the perspective of suitability for semiconductor devices, by making the Al composition ratio x in the composition formula of the substrate 50 greater than 0.05, when the substrate 50 is applied to ultraviolet LEDs or ultraviolet LDs, the transmittance of ultraviolet light of the substrate 50 can be improved. On the other hand, if the Al composition ratio x in the composition formula of the substrate 50 is higher than 0.8, the occurrence of Al vacancies becomes significant. Therefore, the substrate 50 is prone to lose conductivity. In contrast, by making the Al composition ratio x in the composition formula of the substrate 50 less than 0.8, the occurrence of Al vacancies can be suppressed. As a result, the substrate 50 formed of the AlGaN crystal can be given conductivity.
[0198] The diameter of the substrate 50 is, for example, 1 inch (25 mm) or more, or 2 inches (50 mm) or more, or 4 inches (100 mm) or more. The thickness of the substrate 50 is, for example, 300 μm or more and 1 mm or less.
[0199] The substrate 50 has a main surface 50s whose nearest low-index crystal plane is, for example, a c-plane 50c. The main surface 50s of the substrate 50 is, for example, mirror-finished, and the root mean square roughness RMS of the main surface 50s of the substrate 50 is, for example, less than 1 nm.
[0200] In this embodiment, the substrate 50 does not include a polarity inversion region (inversion domain) by growing the regrown layer 500 using, for example, the c-plane as a continuous growth plane.
[0201] In this embodiment, the above-described manufacturing method can alleviate the crystal strain generated in the regrown layer 500 formed of AlGaN crystal. As a result, the substrate 50 obtained from the regrown layer 500 has no cracks.
[0202] In this embodiment, the crystal strain in the substrate 50 obtained by the regrown layer 500 is relaxed by relaxing the crystal strain generated in the regrown layer 500. As a result, the ratio a / c of the lattice constant in the a-axis direction of the substrate 50 to the lattice constant in the c-axis direction is close to the ratio a / c (=0.62) of the strain-free AlGaN crystal.
[0203] Specifically, the substrate 50 satisfies the following formula (1).
[0204] 0.58≤a / c≤0.66…(1)
[0205] Here, c is the lattice constant in the <0001> axis direction of the substrate 50 obtained by X-ray diffraction measurement (2θ-ω scanning) based on the diffraction angle of the peak of diffraction from the (0002) plane of AlGaN.
[0206] a is the lattice constant in the <11-20> axis direction of the substrate 50 obtained based on c and the diffraction angle of the peak of diffraction of the (10-12) plane of AlGaN obtained by X-ray diffraction measurement (2θ-ω scanning).
[0207] In the present embodiment, each of the (0002) plane diffraction and (10-12) plane diffraction patterns of AlGaN obtained in the above-mentioned X-ray diffraction measurement of the substrate 50 has a single peak.
[0208] In this embodiment, by alleviating the crystal strain generated in the regrown layer 500 , the crystallinity of the substrate 50 obtained by the regrown layer 500 can be improved.
[0209] Specifically, the full width at half maximum (FWHM: Full Width at Half Maximum) of the (0002) plane diffraction of AlGaN obtained by measuring the X-ray rocking curve of the substrate 50 may be, for example, 300 arcsec or less, or 100 arcsec or less.
[0210] The full width at half maximum (FWHM) of the (10-12) plane diffraction of AlGaN obtained by measuring the X-ray rocking curve of the substrate 50 is, for example, 500 arcsec or less, or may be 300 arcsec.
[0211] The X-ray rocking curve measurement was performed under the following conditions.
[0212] X-ray: Monochromatic light of Cu Kα1 obtained from an X-ray source via an X-ray reflector and two crystals of Ge (220) plane.
[0213] Gonio radius: 420mm
[0214] Entrance slit width: 0.1mm
[0215] Light receiving slit side: Analytical crystal
[0216] In this embodiment, the regrown layer 500 is not grown in an island shape, but is grown as a continuous film formed of AlGaN crystals, so that the Al composition ratio x in the thickness direction of the regrown layer 500 becomes uniform. As a result, in the substrate 50 obtained from the regrown layer 500, the Al composition ratio xr on the back surface of the substrate 50 is equal to or close to the Al composition ratio xm on the main surface of the substrate 50.
[0217] Specifically, a ratio xm / xr of the Al composition ratio xm in a region 35 μm from the main surface 50s of the substrate 50 along the thickness direction to the Al composition ratio xr in a region 35 μm from the back surface of the substrate 50 along the thickness direction is, for example, greater than 0.9 and less than 1.1.
[0218] The Al composition ratios xr and xm mentioned here are obtained based on the diffraction angle of the peak of (0002) plane diffraction by X-ray diffraction measurement of the back surface and main surface of the substrate 50. The position of "35 μm" from each surface toward the thickness direction is the penetration length from each surface in the X-ray diffraction measurement when using Cu Kα1 rays.
[0219] In the substrate 50 obtained from the regrown layer 500 , the Al composition ratio xo at the periphery of the main surface of the substrate 50 and the Al composition ratio xc at the center of the main surface of the substrate 50 are equal to or close to each other.
[0220] Specifically, a ratio xc / xo of the Al composition ratio xc at the center of the main surface 50s of the substrate 50 to the Al composition ratio xo at a position 5 mm from the periphery toward the center of the main surface 50s of the substrate 50 is, for example, 0.9 or more and 1.1 or less.
[0221] The Al composition ratios xo and xc mentioned here are obtained based on the diffraction angle of the peak of (0002) plane diffraction by X-ray diffraction measurement performed on the outer peripheral side and the center of the main surface of the substrate 50, respectively.
[0222] In this embodiment, dislocations can be reduced during the growth of the thick regrown layer 500 , thereby reducing the dislocation density in the substrate 50 formed of AlGaN crystal obtained from the regrown layer 500 .
[0223] Specifically, the dislocation density of the primary surface 50s of the substrate 50 is, for example, 3×10 8 cm -2 Below, or 1×10 7 cm -2 Below, or 5×10 6 cm -2 Below, or 3×10 6 cm -2 the following.
[0224] The conductivity type of the substrate 50 is not particularly limited. However, the substrate 50 of this embodiment may be, for example, an n-type. In this case, examples of n-type impurities include Si, germanium (Ge), oxygen (O), and tin (Sn). The concentration of n-type impurities in the substrate 50 may be, for example, 1×10 17 cm -3 Above and 1×10 19 cm -3 the following.
[0225] Alternatively, the substrate 50 of this embodiment may be, for example, a p-type. In this case, the substrate 50 may contain, for example, magnesium (Mg). The Mg concentration in the substrate 50 may be, for example, 1×10 16 cm -3 above.
[0226] Alternatively, the substrate 50 of this embodiment may be semi-insulating, for example. In this case, the substrate 50 may contain, for example, iron (Fe), manganese (Mn), or carbon (C). The concentration of Fe, Mn, or C in the substrate 50 may be, for example, 1×10 16 cm -3 above.
[0227] (3) Summary of this embodiment
[0228] According to this embodiment, one or more of the following effects can be obtained.
[0229] (a) In this embodiment, a regrown layer 500 composed of AlGaN crystal is grown on the cap layer 400 provided on the porous intermediate layer 300 , so that the stress applied to the regrown layer 500 can be relaxed by utilizing the easily deformable porous intermediate layer 300 .
[0230] (b) Furthermore, by growing the regrown layer 500 formed of AlGaN crystal on the flat cap layer 400, the regrown layer 500 can be grown as a continuous film while suppressing the island growth of the regrown layer 500. Thus, the Al composition ratio x can be made uniform throughout the regrown layer 500.
[0231] By growing the regrown layer 500 as in (a) and (b), the crystal strain occurring in the regrown layer 500 formed of AlGaN can be alleviated. Thus, the occurrence of cracks in the regrown layer 500 can be suppressed. In addition, the crystallinity of the regrown layer 500 can be improved. As a result, a substrate 50 formed of high-quality AlGaN crystal can be stably obtained from the regrown layer 500.
[0232] By using the above-described substrate 50 obtained in this embodiment mode, for example, a high-quality semiconductor device such as an ultraviolet LED or an ultraviolet LD can be manufactured.
[0233] (c) In the present embodiment, the crystal strain applied to the regrown layer 500 is relaxed, and at the same time, appropriate crystal strain can be applied to the porous intermediate layer 300 .
[0234] By setting the Al composition ratio x of the regrown layer 500 to be 0.05 or more, as the regrown layer 500 grows, due to the lattice mismatch between the regrown layer 500 and the layer located below the regrown layer 500, appropriate crystal strain can be applied to the porous intermediate layer 300. As a result, the fragility of the porous intermediate layer 300 can be increased. As a result, the peeling property of the regrown layer 500 with the intermediate layer 300 as a boundary can be improved.
[0235] On the other hand, by setting the Al composition ratio x of the regrown layer 500 to 0.8 or less, it is possible to suppress excessive crystal strain in the porous intermediate layer 300 caused by lattice mismatch between the regrown layer 500 and the layer located below the regrown layer 500. As a result, it is possible to suppress the disappearance of the voids 360 in the intermediate layer 300 and suppress the bonding between the regrown layer 500 and the layer located below the regrown layer 500. As a result, it is possible to suppress the reduction in the peeling property of the regrown layer 500 bounded by the intermediate layer 300.
[0236] As described above, from the viewpoint of the peeling property of the regrown layer 500 , the substrate 50 formed of the AlGaN crystal can be stably obtained.
[0237] (4) Modification of one embodiment
[0238] The above-mentioned embodiment can be modified as required as in the following modified examples. Hereinafter, only the elements different from the above-mentioned embodiment will be described, and the elements substantially the same as those described in the above-mentioned embodiment are given the same reference numerals and their descriptions are omitted.
[0239] (Variant 1)
[0240] In the cover layer forming step S40 of the modification example 1, for example, Al may be used as the cover layer 400. x Ga 1-x A crystal represented by a composition formula of N grows. At this time, the Al composition ratio x of the cap layer 400 is set to, for example, higher than 0 and less than 1, or may be set to 0.05 or more and 0.8 or less.
[0241] According to Modification 1, by growing AlGaN crystal as the cap layer 400, the regrown layer 500 can be homoepitaxially grown on the cap layer 400. Thus, the regrown layer 500 having good crystallinity can be stably grown.
[0242] (Variant 2)
[0243] In the first regrowth step S62 of Modification 2, the first regrowth layer 520 may be grown while the growth temperature is gradually increased from the first growth temperature T1 to the second growth temperature T2.
[0244] According to Modification 2, the heating rate from the first growth temperature T1 to the second growth temperature T2 can be slowed down. As a result, cracks in the group III nitride crystal layer above the intermediate layer 300 caused by the heating process from the first growth temperature T1 to the second growth temperature T2 can be stably suppressed.
[0245] (Variant 3)
[0246] In the regrowth step S60 of Modification 3, the growth temperature of the regrowth layer 500 can be adjusted in one step. That is, the temperature of the seed substrate 10 can be directly increased from room temperature to the growth temperature of the regrowth step S60 (equivalent to the second growth temperature T2 described above).
[0247] According to Modification 3, the first regrowth step S62 can be omitted. As a result, the manufacturing process can be shortened.
[0248] <Other embodiments of the present invention>
[0249] The embodiments of the present invention have been specifically described above, but the present invention is not limited to the above-described embodiments, and various modifications can be made without departing from the spirit and scope of the present invention.
[0250] In the above embodiment, the case where the base layer forming step S20 is performed is described, but the base layer forming step S20 may not be performed. In other words, the base layer 200 may not be provided. In the intermediate layer forming step S30 , the intermediate layer 300 may be formed directly on the base substrate 100 .
[0251] In the above-mentioned embodiment, the upper layer of the bottom layer 200 and the middle layer 300 respectively contain GaN crystals, but the present invention is not limited to this case. Each layer is not limited to GaN crystals, for example, it can also be formed of a III-group nitride crystal such as aluminum nitride (AlN), aluminum gallium nitride (AlGaN), indium nitride (InN), indium gallium nitride (InGaN), aluminum indium gallium nitride (AlInGaN), etc., that is, In x Al y Ga 1-x-y A crystal represented by the composition formula of N (wherein 0≤x≤1, 0≤y≤1, 0≤x+y≤1) is formed.
[0252] In the above embodiment, the base substrate 100 is described as being made of a material other than group III nitride, but the present invention is not limited to this case. The base substrate 100 may be, for example, a free-standing substrate made of a group III nitride crystal.
[0253] In the above-mentioned embodiment, the case where the upper layer of the bottom layer 200, the middle layer 300, the covering layer 400 and the regrown layer 500 contain Si as an n-type impurity is described, but at least one layer of the upper layer of the bottom layer 200, the middle layer 300, the covering layer 400 and the regrown layer 500 may also contain, for example, O or Ge as an n-type impurity.
[0254] In the above-mentioned embodiment, the above-mentioned vapor phase growth methods are used as the growth methods of the base layer 200, the intermediate layer 300, the cover layer 400 and the regrown layer 500, but the present invention is not limited to such a case. As the growth method of at least any one of the base layer 200, the intermediate layer 300, the cover layer 400 and the regrown layer 500, the metal organic vapor phase growth (MOVPE) method may be used. Alternatively, as the growth method of at least any one of the base layer 200, the intermediate layer 300, the cover layer 400 and the regrown layer 500, a growth method other than the vapor phase growth method may be used.
[0255] In the above embodiment, the first regrown layer 520 is three-dimensionally grown after the step flow growth at the initial growth stage of the first regrown layer 520 , but the present invention is not limited to this case. The step flow growth of the first regrown layer 520 may be maintained.
[0256] Example
[0257] Hereinafter, experimental results confirming the effects of the above-described embodiment will be described.
[0258] (1) Sample preparation
[0259] The following three samples were prepared.
[0260] [Sample A]
[0261] By the manufacturing method of the above-described embodiment, a nitride crystal substrate of Sample A was prepared according to the following procedure.
[0262] (Base substrate preparation process)
[0263] A base substrate for obtaining a seed substrate is prepared.
[0264] Base substrate: sapphire substrate
[0265] The plane orientation of the main surface of the base substrate: +c plane
[0266] Diameter of base substrate: 2 inches (50.8 mm)
[0267] Thickness of base substrate: 430 μm
[0268] (Base layer forming process)
[0269] By the HVPE method, an AlN buffer layer and a GaN layer were formed in this order as a bottom layer on a base substrate under the following conditions.
[0270] Growth temperature of the bottom layer: 1055℃.
[0271] The thickness of the AlN buffer layer and the GaN layer are 100nm and 4μm respectively.
[0272] Carrier concentration in the GaN layer as the bottom layer: about 1×10 18 cm -3
[0273] (Intermediate Layer Formation Step)
[0274] Next, a Si-doped GaN layer was grown as an intermediate layer on the underlying layer by the HVPE method under the following conditions.
[0275] Growth temperature of the middle layer: 1055°C.
[0276] Thickness of the middle layer: 3000nm
[0277] Carrier concentration in the middle layer: 6×10 18 cm -3
[0278] (Coating Layer Forming Step)
[0279] Next, a GaN layer was grown as a cap layer on the underlying layer by the HVPE method under the following conditions.
[0280] Growth temperature of the covering layer: 1055°C.
[0281] Thickness of cover layer: 150nm
[0282] Carrier concentration in the cover layer: about 5×10 17 cm -3
[0283] (Porous process)
[0284] Next, by electrochemical treatment under the following conditions, the intermediate layer is made porous due to dislocation of the cover layer.
[0285] Electrolyte temperature: room temperature (23°C)
[0286] Processing voltage: 20V
[0287] Processing current: Maximum 100mA
[0288] Processing time: 10 minutes
[0289] (First Regrowth Step)
[0290] Next, Al was deposited on the cap layer by HVPE under the following conditions: 0.6 Ga 0.4 The N layer grows as the first regrown layer.
[0291] First growth temperature: 835°C.
[0292] Thickness of the first regrown layer: 50 μm
[0293] (Second Regrowth Step)
[0294] Next, in the same chamber as the first regrowth step, Al 0.6 Ga 0.4 The N layer grows as a second regrown layer.
[0295] Second growth temperature: 1055℃.
[0296] Total thickness of the regrown layer: 1 mm
[0297] (Peeling process)
[0298] During the temperature drop after the regrowth step, the regrowth layer is peeled off from the base substrate.
[0299] (Post-processing process)
[0300] The peeled regrown layer was sliced to form a nitride crystal substrate. After slicing, both sides of the nitride crystal substrate were polished to obtain a 430 μm thick Al 0.6 Ga 0.4 A nitride crystal substrate formed of N crystal was used as Sample A1.
[0301] [Sample B1 (Direct Growth on GaN Free-standing Substrate)]
[0302] In the preparation of sample B1, a GaN self-supporting substrate was used as the base substrate. A 1 mm thick Al layer was deposited directly on the GaN self-supporting substrate by HVPE under the same conditions as those for the second regrown layer of sample A. 0.6 Ga 0.4 The N layer was grown as the main growth layer. Thus, a laminate of Sample B1 was obtained.
[0303] [Sample B2 (VAS method)]
[0304] The VAS method was used to prepare sample B2. First, a template was prepared, which had a GaN layer with a thickness of 300 nm and a void, and a TiN layer with a thickness of 20 nm in a mesh shape, on a sapphire substrate with a diameter of 2 inches. Next, a 1 mm thick Al layer was grown on the GaN layer and TiN layer by HVPE under the same conditions as the second regrown layer of sample A. 0.6 Ga 0.4 The N layer was grown as the main growth layer. Then, the main growth layer was peeled off from the sapphire substrate with the GaN layer having voids as the boundary. Thus, the Al0.6 Ga 0.4 N layers.
[0305] (2) Evaluation [Optical Microscope]
[0306] Each sample was observed using an optical microscope.
[0307] [X-ray diffraction measurement]
[0308] In the nitride crystal substrate of sample A, X-ray diffraction measurement (2θ-ω scanning) of (0002) plane diffraction and (10-12) plane diffraction of AlGaN was performed. The measurement positions include: the center of the main surface of the nitride crystal substrate of sample A; points set at intervals of 1 cm on a straight line passing through the center of the main surface and along the m-axis direction; points set at intervals of 1 cm on a straight line passing through the center of the main surface and along the a-axis direction orthogonal to the m-axis direction. Based on the results obtained by the X-ray diffraction measurement, a / c of the nitride crystal substrate of sample A was obtained.
[0309] In addition, by performing X-ray diffraction measurement on the nitride crystal substrate of sample A, the ratio xc / xo was calculated based on the Al composition ratio xc at the center of the main surface of the substrate relative to the Al composition ratio xo at a position 5 mm from the periphery toward the center of the main surface of the substrate.
[0310] In addition, at each of the above-mentioned measurement positions where the main surface and the back surface of the nitride crystal substrate of sample A overlap with each other, by performing X-ray diffraction measurement, the ratio xm / xr is calculated based on the Al composition ratio xm in the area from the main surface of the substrate to the position of 35 μm in the thickness direction relative to the Al composition ratio xr in the area from the back surface of the substrate to the position of 35 μm in the thickness direction.
[0311] [X-ray rocking curve measurement]
[0312] By performing X-ray rocking curve measurement at each of the above-mentioned measurement positions of the nitride crystal substrate of Sample A, the full width at half maximum (FWHM) of the (0002) plane diffraction and (10-12) plane diffraction of AlGaN was obtained.
[0313] [Multiphoton Excitation Microscopy]
[0314] At each of the above-mentioned measurement positions of the nitride crystal substrate of Sample A, the dislocation density was determined by observing the main surface in a 250 μm square field of view using a multiphoton excitation microscope.
[0315] (3) Results
[0316] The results of samples A, B1, and B2 will be described.
[0317] [Sample B1]
[0318] In sample B1, cracks occurred in the main growth layer after the growth of the main growth layer on the GaN self-supporting substrate. In sample B1, it is believed that the main growth layer cracked due to lattice mismatch between the GaN self-supporting substrate and the main growth layer formed of AlGaN crystal.
[0319] [Sample B2]
[0320] In sample B2, a portion of the main growth layer peeled off from the sapphire substrate cracked. In sample B2, when the island-shaped AlGaN crystals grow three-dimensionally on the GaN layer containing voids and the mesh-shaped TiN layer, the movement of Al atoms is small. Therefore, the Al composition ratio deviates within the plane. Due to the deviation of the Al composition ratio, crystal strain is generated in the main growth layer formed by the thick film AlGaN crystal. As a result, it is believed that in sample B2, cracks occurred in the main growth layer.
[0321] [Sample A]
[0322] In Sample A, the peeled regrown layer and the nitride crystal substrate obtained from the regrown layer did not develop cracks.
[0323] In sample A, the crystal strain occurring in the regrown layer can be alleviated by growing a regrown layer formed of AlGaN crystal on a flat cap layer provided on a porous intermediate layer. The results confirm that in sample A, a high-quality nitride crystal substrate formed of AlGaN crystal without cracks can be obtained.
[0324] Furthermore, when other analyses were performed on the nitride crystal substrate of Sample A, it was confirmed that the following characteristics were obtained.
[0325] Al composition ratio xc / xo: 1.07
[0326] It was also confirmed that the following characteristics can be obtained at each measurement position set at intervals of 1 cm on a straight line passing through the center of the main surface and along the m-axis direction, including the center of the main surface of the nitride crystal substrate of sample A, and on a straight line passing through the center of the main surface and along the a-axis direction orthogonal to the m-axis direction.
[0327] 0.58≤a / c≤0.66…(1)
[0328] (0002) plane diffraction FWHM<250arcsec
[0329] (10-12) plane diffraction FWHM<450arcsec
[0330] Dislocation density<3×10 6 cm -2
[0331] It was also confirmed that the following characteristics were obtained at measurement positions set at intervals of 1 cm on a straight line passing through the center of the main surface and the back surface and along the m-axis direction, including the center of the main surface and the back surface of the nitride crystal substrate of sample A, and on a straight line passing through the center of the main surface and the back surface and along the a-axis direction orthogonal to the m-axis direction.
[0332] Al composition ratio xm / xr: 0.95 to 1.05
[0333] Al composition ratio x: 0.59 to 0.63
[0334] <Notes>
[0335] Hereinafter, aspects of the present invention will be supplemented.
[0336] (Note 1)
[0337] A method for manufacturing a nitride crystal substrate, comprising the following steps:
[0338] (a) a step of preparing a base substrate;
[0339] (b) forming an intermediate layer containing n-type group III nitride crystals on the base substrate;
[0340] (c) forming, on the intermediate layer, a cap layer containing a Group III nitride crystal having a carrier concentration lower than that of the intermediate layer;
[0341] (d) a step of maintaining the surface state of the covering layer and making the intermediate layer porous by dislocation of the covering layer through electrochemical treatment;
[0342] (e) a step of epitaxially growing a regrown layer formed of a group III nitride crystal on the cap layer;
[0343] (f) a step of peeling the regrown layer from the base substrate with at least a portion of the intermediate layer formed into a porous state as a boundary,
[0344] In (e), the Al composition ratio x is set to be 0.05 or more and 0.8 or less. x Ga 1-x A crystal represented by the composition formula of N is grown as the regrown layer.
[0345] (Note 2)
[0346] The method for manufacturing a nitride crystal substrate according to Supplementary Note 1, wherein in (e), crystal strain occurring in the regrown layer is relaxed compared to a case where (d) is not performed.
[0347] (Note 3)
[0348] The method for manufacturing a nitride crystal substrate according to Supplementary Note 1 or Supplementary Note 2, wherein in (e), the regrown layer is subjected to step flow growth at least in an initial stage of growth of the regrown layer.
[0349] (Note 4)
[0350] The method for manufacturing a nitride crystal substrate according to any one of Supplementary Notes 1 to 3, wherein in (c), GaN crystal is grown as the cap layer.
[0351] (Note 5)
[0352] The method for manufacturing a nitride crystal substrate according to any one of Supplementary Notes 1 to 3, wherein in (c), the Al composition ratio x is set to be higher than 0 and less than 1. x Ga 1-x A crystal represented by the composition formula of N is grown as the cap layer.
[0353] (Note 6)
[0354] The method for manufacturing a nitride crystal substrate according to any one of Notes 1 to 5, wherein (e) comprises the following steps:
[0355] (e1) a step of growing a first regrown layer on the cap layer at a first growth temperature;
[0356] (e2) a step of growing a second regrown layer on the first regrown layer at a second growth temperature,
[0357] In (e1), the first growth temperature is set lower than the second growth temperature.
[0358] (Note 7)
[0359] A nitride crystal substrate, wherein
[0360] Contains Al x Ga 1-x A crystal represented by the composition formula of N,
[0361] The Al composition ratio x in the composition formula is 0.05 or more and 0.8 or less,
[0362] The nitride crystal substrate satisfies the following formula (1),
[0363] 0.58≤a / c≤0.66…(1)
[0364] Here,
[0365] c is the lattice constant in the <0001> axis direction of the nitride crystal substrate obtained by measuring the diffraction angle of a peak based on the (0002) plane diffraction of AlGaN by X-ray diffraction,
[0366] a is the lattice constant in the <11-20> axis direction of the nitride crystal substrate obtained based on c and the diffraction angle of the peak of (10-12) plane diffraction of AlGaN obtained by X-ray diffraction measurement.
[0367] (Note 8)
[0368] The nitride crystal substrate according to Supplementary Note 7, wherein the nitride crystal substrate has a diameter of 25 mm or more and has no cracks.
[0369] (Note 9)
[0370] The nitride crystal substrate according to Supplementary Note 7 or Supplementary Note 8, wherein the full width at half maximum of diffraction of (0002) plane of AlGaN obtained by X-ray rocking curve measurement of the nitride crystal substrate is 300 arcsec or less,
[0371] The full width at half maximum of (10-12) plane diffraction of AlGaN obtained by X-ray rocking curve measurement of the nitride crystal substrate is less than 500 arcsec.
[0372] (Note 10)
[0373] The nitride crystal substrate according to any one of Supplementary Notes 7 to 9, wherein the nitride crystal substrate has a main surface and a back surface opposite to the main surface,
[0374] A ratio xm / xr of an Al composition ratio xm in a region from the main surface of the nitride crystal substrate to a position of 35 μm in the thickness direction to an Al composition ratio xr in a region from the back surface of the nitride crystal substrate to a position of 35 μm in the thickness direction is 0.9 or more and 1.1 or less.
[0375] (Note 11)
[0376] A nitride crystal substrate according to any one of Notes 7 to 10, wherein a ratio xc / xo of an Al composition ratio xc of the nitride crystal substrate at the center of the main surface relative to an Al composition ratio xo of the nitride crystal substrate at a position 5 mm from the periphery of the main surface toward the center is greater than 0.9 and less than 1.1.
[0377] (Note 12)
[0378] A laminated article, comprising:
[0379] The nitride crystal substrate according to any one of Notes 7 to 11;
[0380] A semiconductor layer containing a group III nitride crystal is provided on the nitride crystal substrate.
Claims
1. A method for manufacturing a nitride crystal substrate, wherein: The following processes are available: (a) a step of preparing a base substrate; (b) forming an intermediate layer containing n-type group III nitride crystals on the base substrate; (c) forming, on the intermediate layer, a cap layer containing a Group III nitride crystal having a carrier concentration lower than that of the intermediate layer; (d) a step of maintaining the surface state of the covering layer and making the intermediate layer porous by dislocation in the covering layer through electrochemical treatment; (e) a step of epitaxially growing a regrown layer including a group III nitride crystal on the cap layer; (f) a step of peeling the regrown layer from the base substrate with at least a portion of the intermediate layer formed into a porous state as a boundary, In (e), as the regrown layer, the Al composition ratio x is 0.05 or more and 0.8 or less. x Ga 1-x The crystal growth represented by the composition formula of N.
2. The method for manufacturing a nitride crystal substrate according to claim 1, wherein: In (e), at least in the initial stage of growth of the regrown layer, the regrown layer is subjected to step flow growth.
3. The method for manufacturing a nitride crystal substrate according to claim 1 or claim 2, wherein: In (c), GaN crystal is grown as the cap layer.
4. The method for manufacturing a nitride crystal substrate according to claim 1 or claim 2, wherein: In (c), as the capping layer, a layer composed of Al having an Al composition ratio x of greater than 0 and less than 1 is used. x Ga 1-x The crystal growth represented by the composition formula of N.
5. A nitride crystal substrate, wherein: Contains Al x Ga 1-x A crystal represented by the composition formula of N, The Al composition ratio x in the composition formula is 0.05 or more and 0.8 or less, The nitride crystal substrate satisfies the following formula (1), 0.58≤a / c≤0.66…(1) Here, c is the lattice constant in the <0001> axis direction of the nitride crystal substrate obtained by measuring the diffraction angle of a peak based on the (0002) plane diffraction of AlGaN by X-ray diffraction, a is the lattice constant in the <11-20> axis direction of the nitride crystal substrate obtained based on c and the diffraction angle of the peak of (10-12) plane diffraction of AlGaN obtained by X-ray diffraction measurement.
6. The nitride crystal substrate according to claim 5, wherein The nitride crystal substrate has a diameter of 25 mm or more and has no cracks.
7. The nitride crystal substrate according to claim 5 or claim 6, wherein: The nitride crystal substrate has a full width at half maximum of 300 arcsec or less of diffraction of the (0002) plane of AlGaN obtained by X-ray rocking curve measurement, The full width at half maximum of (10-12) plane diffraction of AlGaN obtained by X-ray rocking curve measurement of the nitride crystal substrate is less than 500 arcsec.
Citation Information
Patent Citations
Iii group nitride semiconductor substrate, and method for manufacturing it
JP2003178984A